A replicated study of communication networks, job retention and labour turnover in two British hotels - McEwan, T. (Cranfield University, 1988)
Human communication is examined from several standpoints and an 'Exchange' perspective is preferred because its of greater explanatory power in reconciling Communication and Organisational theory, when the latter is concetualised as Open Systems theory. This synthesis provides a rationale for analysing exchanges between the members of organsiations involved in both Prescribed networks, comprising information, goods and decision transactions; and Emergent networks which also include Friendship transactions. An inductive methodology is used to analyse networks of perceived and received communication links so that dyadic, clique and system measures of Connectedness can be calculated. Replicated communication surveys and labour turnover analyses are described for two hotels, after the various jobs undertaken were grouped under six Job Classifications, according to the individual roles in internal and external communication networks, so that network analysis could be completed at progressively more complex levels of generality and the relationships between Connectedness and Labour Turnover, and the analysis of the hotels under a 'Grid/Group' taxonomy, could be investigated. Five main hypotheses are tested which postulate that Connectedness is related posively to length of employment, higher job status, and negatively to labour turnover. Subject to the mediating influence of age, pay, and length of full-time education and company training, strong correlations occurred between the Connectedness of isolated, lower-status individuals and Labour Turnover. Members of the higher-status Job Classifications were more common in the longer-employed dominant cliques at the Coastal hotel, where the 'Grid/ Group' characteristics of 'Insulated Subordination' were reinforced by kinship ties and friendship links established away from work or in previous employment. The characteristics of 'Collaborative and Competitive Alliances' predominated at the London hotel, where most higher-status members were excluded from dominant cliques which typically consisted of supervisors and long-serving members of the three main ethnic minority groups.